Multi-criteria analysis of nuclear power in the global energy system: Assessing trade-offs between simultaneously attainable economic, environmental and social goals. (July 2015) - Lehtveer, Mariliis; Makowski, Marek; Hedenus, Fredrik; McCollum, David; Strubegger, Manfred
Abstract: To investigate the complex relationships among the energy-related challenges faced by humanity, we marry a large-scale energy systems model, MESSAGE, with a multi-criteria model analysis tool. Such an approach is applicable to other modelling frameworks and can significantly improve the analysis of multiple goals. We focus our study on nuclear power – a technology viewed differently by different stakeholders. We find that nuclear power plays an important role in global climate change mitigation efforts where energy security and affordability goals take precedence, but that the total amount of nuclear in the system is highly dependent on stakeholders' preferences. We also find synergies among climate mitigation and energy security goals, and also between these two goals and the reduced need for underground carbon storage. Highlights: High priority of energy security in combination with climate targets enhances the role of nuclear power. Focussing on both climate and energy security goals lessens the need for CCS and thus the dependency on storage availability. The optimal amount of nuclear power in the energy system strongly depends on the stakeholder's preferences. MCMA can significantly improve the analysis of attainability of multiple simultaneous goals in large scale energy models.